Konsep dan Kajian Teori Perumusan Kebijakan Publik - Muadi, Sholih; MH, Ismail; Sofwani, Ahmad (Jurnal Review Politik, 2016)
The objective of this research was to describe concepts and theoretical reviews relevant with public policy formulation. Method of research was the review of theories or literatures. Result indicated that concepts and theories, mainly those relevant with public policy formulation, or that were previously used by policy experts, can be then used for all fields of policy science. Some reviews and theories of policy formulation may resolve policy issues that already challenged organizations or institutions, either those in government or private sector.